The Resilience of urban agriculture in the European context - Maicol Negrello; Daniele Roccaro; Kevin Santus; Isabella Spagnolo (Agathón)
The growing phenomena linked to climate change pushes cities to develop resilience plans to respond to environmental, social, and economic sustainability. Nature-based strategies can be a solution; among these, urban agriculture can increase the resilience of European urban fabrics. This activity has been the object of interest several times during crises or as a community activity with social, productive, and educational characteristics. Through a historical excursus and a subsequent analysis of contemporary case studies, the paper provides design tools for intervening in the built environment with strategies ranging from the urban to the architectural scale. The essay presents a replicable morpho-typological approach that can be applied and used by planners and policymakers to increase urban resilience.